ANALISIS PERDAGANGAN INTRA-INDUSTRI INDONESIA TERHADAP MITRA DAGANG ASEAN-4 DAN ASIA TIMUR (Studi Kasus : Pada Sektor Manufaktur Tahun 2010-2015) - Purba, Debora Angelia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The objective of this research is to find out intra-industry trade in manufactures from Indonesia to trading partners ASEAN-4 and East Asia. Indonesia’s intra- industry trade measurement to trading partners is estimated by Grubel-Lloyd index and analyzed by panel data approach. This research will take period 2010-2015. The estimated intra-industry trade indexes demonstrates that there is a difference integration, that is strong to very strong integration in Thailand, Malaysia, Singapore, Japan and South Korea. While, Philippines and China in medium integration. The result shows the determinants of intra-industry trade including economic scale, demand structure, geographical distance, and exchange rate have significant effect on intra-industry trade between Indonesia and its trading partner.Keywords: Intra-industry trade, manufactures.